Treatment of relapsed AML and MDS after allogeneic stem cell transplantation with decitabine and DLI: a retrospective multicenter analysis on behalf of the German Cooperative Transplant Study Group - Schroeder, Thomas; Rautenberg, Christina; Krüger, William H.; Platzbecker, Uwe; Bug, Gesine; Steinmann, Juliane; Klein, Stefan; Hopfer, Olaf; Nachtkamp, Kathrin; Kondakci, Mustafa; Geyh, Stefanie; Haas, Rainer; et al. (Annals of hematology, 2018)
In contrast to the evidence regarding azacitidine (Aza), there is limited knowledge about the combination of decitabine (DAC) and donor lymphocyte infusions as salvage therapy for relapse after allogeneic stem cell transplantation (allo-SCT) so far. We retrospectively analyzed data of 36 patients with hematological (n = 35) or molecular relapse (n = 1) of acute myeloid leukemia (AML, n = 29) or myelodysplastic syndrome (MDS, n = 7) collected from 6 German transplant centers. Patients were treated with a median of 2 cycles DAC (range, 1 to 11). DAC was the first salvage therapy in 16 patients (44%), whereas 20 patients (56%) had previously received 1 to 5 lines of salvage therapy including 16 of them had been treated with Aza. In 22 patients (61%), a median of 2 DLI per patient (range, 1 to 5) was administered in addition to DAC. As a result, overall response rate was 25% including 6 complete remissions (CR, 17%) and 3 partial remissions (PR, 8%). Three patients within the first-line group achieved CR, while also 3 patients receiving DAC as second-line treatment reached CR including 2 patients with previous Aza failure. Median duration of CR was 10 months (range, 2 to 33) and no patient relapsed so far. The 2-year OS rate was 11% (± 6%) without any difference between first-line and pretreated patients. Incidence of acute and chronic graft-versus-host disease was 19 and 5%. Taken together, DAC exerts clinical efficacy in patients with AML or MDS relapsing after allo-SCT and is able to induce durable remissions in individual patients suggesting that DAC may be an alternative to Aza or even a second choice after Aza failure.